مشكلة تعليم اللغة العربية وتعلّمها - الرماح.د. علي أحمد (Aljameai)
المستخلص: يتناول هذا البحث مشكلة تعليم اللغة العربية وتعلمها في المؤسسات التعليمية عبر مراحل التعليم الأساس والمتوسطة والجامعية، ويرصد مسببات مشكلتي القصور اللغوي، والعزوف اللغوي، ويضع تصورا منهجيا جديدا نابعا من التراث اللغوي العربي، والمسلك العربي الأصيل، والأبجدية التي اتبعها العرب الأقحاح وتمكنوا بها من اللغة العربية، وتدرجت من المهارات الأساسية، سماعا، وقراءة، وكتابة، وتحدثا، وصولا إلى التذوق العامل المحفز للإقبال على اللغة العربية، والصياغة اللغوية الرصينة والصحيحة، والترغيب والتحفيز والإقبال على تعلم اللغة العربية، والقضاء على مشكلتي القصور اللغوي، والعزوف اللغوي، وصولا إلى التمكن من صناعة المحتوى، ومجاراة التطورات التكنولوجية ذات العلاقة باللغة، والقدرة على تحقيق التواصل مع اللغات الأخرى. Abstract: This research deals with the problem of teaching and learning the Arabic language in educational institution across the basic education, intermediate, and university level of education .It monitors the causes of the problems of linguistic deficiency and reluctance, and sets a new methodological vision stemming from the Arab linguistic heritage, the authentic Arabic method , and the alphabet that the ancient Arabs followed and with which they mastered the Arabic language, and acquired from Basic skills: listen, reading, writing, and speaking, all the way to taste, the motivating factor for interest . The Arabic language, clear and correct linguistic formulation, encouragement, motivation and desire to learn. The Arabic language, eliminating the problems of insufficiency and reluctance, leading to mastery of creation content, keeping up with technological developments related to language, and the ability to communicate with other languages.